TANTANGAN GEREJA DALAM MENGATASI TERJADINYA PERGAULAN BEBAS DI KALANGAN REMAJA KRISTEN - Depi Iman Nius Gulo; Monica Santosa (MAWAR SARON: Jurnal Pendidikan Kristen dan Gereja, 2025)
This article reviews the church's challenges in overcoming promiscuity among Christian teenagers. Where teenagers are also the future generation of a church who have an important role for the church, the character and attitudes of teenagers are always in the spotlight. However, today's teenagers are more likely to commit deviant acts due to promiscuity, therefore the church is urgently needed to guide and direct teenagers so that they do not deviate in ways that are not in accordance with religious values/norms. The purpose of writing this article is to provide an explanation that promiscuity is a church challenge for the growth of Christian youth.